An investigation into perception of change in the foot-floor interface during repeated stretch-shortening cycles - Travers, Mervyn Joseph (Curtin University, 2014)
Proprioceptive input is critical for normal and safe movement. There exists a gap in the literature regarding the assessment of proprioceptive function during dynamic tasks of the lower limb. To fill this gap, the present thesis has investigated perception of change in the foot-floor interface during repeated stretch-shortening cycles. This doctoral research serves as a foundation for considering proprioception as it pertains to dynamic function at the ankle.